Cardiac calcification following severe sepsis: A case report and review of the literature - ÇİMŞİT, NURİ ÇAGATAY; KARAKURT, SAİT (OMICS Publishing Group, 2014)
There are two types of myocardial calcification: metastatic calcification that is encountered in chronic renal disease patients and dystrophic calcification which develops in injured myocardium. Myocardial infarction, trauma, surgery and myocarditis are the most commonly faced reasons for dystrophic calcification. Here we present a rare case of a patient in whom myocardial calcification was diagnosed after severe sepsis. © 2014 Akbaş T, et al.
Keywords: Myocardial calcifcation; Sepsis-related myocardial injury